Cytonuclear Coevolution following Homoploid Hybrid Speciation in Aegilops tauschii. (16th November 2018) - Li, Changping; Sun, Xuhan; Conover, Justin L; Zhang, Zhibin; Wang, Jinbin; Wang, Xiaofei; Deng, Xin; Wang, Hongyan; Liu, Bao; Wendel, Jonathan F; Gong, Lei
Abstract: The diploid D-genome lineage of the Triticum / Aegilops complex has an evolutionary history involving genomic contributions from ancient A- and B/S-genome species. We explored here the possible cytonuclear evolutionary responses to this history of hybridization. Phylogenetic analysis of chloroplast DNAs indicates that the D-genome lineage has a maternal origin of the A-genome or some other closely allied lineage. Analyses of the nuclear genome in the D-genome species Aegilops tauschii indicate that accompanying and/or following this ancient hybridization, there has been biased maintenance of maternal A-genome ancestry in nuclear genes encoding cytonuclear enzyme complexes (CECs). Our study provides insights into mechanisms of cytonuclear coevolution accompanying the evolution and eventual stabilization of homoploid hybrid species. We suggest that this coevolutionary process includes likely rapid fixation of A-genome CEC orthologs as well as biased retention of A-genome nucleotides in CEC homologs following population level recombination during the initial generations.